2020
DOI: 10.4103/eus.eus_15_20
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pediatric esophageal wall thickness: An EUS study

Abstract: Background and Objective: EUS has been shown in two small series to be capable of documenting increases in the total esophageal wall thickness (TWT) in children and adults with eosinophilic esophagitis (EoE). To apply EUS-derived TWT in clinical situations or in scientific investigations in pediatric EoE, measurements of esophageal TWT in children of differing ages and heights are required. Materials and Methods: Thirty patients (18M: 12F, 7 months to 20 years and 10 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The findings of a study showed that the thickness of mucosa and sub-mucosa and total wall thickness of the middle and distal esophagus increase as a function of the age and height of children. There was an insignificant difference between recorded values for central and distal esophagus, and the obtained values for control patients could be used for determining esophageal disease among children (26). We found no significant difference between the three groups regarding mucosal thickness in the cervical esophagus and diameter and length in the abdominal esophagus.…”
Section: Discussionmentioning
confidence: 49%
“…The findings of a study showed that the thickness of mucosa and sub-mucosa and total wall thickness of the middle and distal esophagus increase as a function of the age and height of children. There was an insignificant difference between recorded values for central and distal esophagus, and the obtained values for control patients could be used for determining esophageal disease among children (26). We found no significant difference between the three groups regarding mucosal thickness in the cervical esophagus and diameter and length in the abdominal esophagus.…”
Section: Discussionmentioning
confidence: 49%
“…D-EUS tends to replace endoscopic retrograde cholangiopancreatography as a diagnostic tool for pancreatobiliary diseases, both in adults and children. EUS contributes to the diagnosis of conditions found only in children, such as congenital anomalies, solid pseudopapillary neoplasia, and certain anorectal disorders (13,26) . In the present study, 81 (76%) procedures were performed to evaluate pancreaticobiliary diseases (TABLE 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, for EUS to be employed in children as a tool to evaluate esophageal wall thickening, normal values of thickness need be obtained. The literature has unfortunately not provided reliable measurements as has been previously summarized 30 . Until the completion of puberty, a child's body will be growing, including the esophageal wall.…”
Section: Endoscopic Ultrasound In Eosinophilic Esophagitismentioning
confidence: 99%